Beneficial Effects of Graded Levels of Fish Protein Hydrolysate (FPH) on the Growth Performance, Blood Biochemistry, Liver and Intestinal Health, Economics Efficiency, and Disease Resistance to Aeromonas hydrophila of Pabda (Ompok pabda) Fingerling - Afrina Yeasmin Suma; Shishir Kumar Nandi; Zulhisyam Abdul Kari; Khang Wen Goh; Lee Seong Wei; Albaris B. Tahiluddin; Paul Seguin; Mikael Herault; Abdullah Al Mamun; Guillermo Téllez-Isaías; Muhammad Anamul Kabir (Fishes, 2023)
Fish protein hydrolysate (FPH) is the enzymatic hydrolysis of protein into smaller peptide and free amino acids, which has recently captured considerable attention as a supplementary ingredient in the aqua-feed industry sector. The present research aimed to observe the physiological, biochemical, and bacteriological study of FPH-treated diets and its effects on growth, hematology, plasma biochemistry, liver and gut histopathology, and resistance to Aeromonas hydrophila infection in Pabda (Ompok pabda). Four experimental diets (35% crude protein) were formulated with graded FPH supplementation (0, 0.5, 1, and 2%). The feed physiological parameters such as expansion ratio, bulk density, water stability, and floatability were not significantly affected by dietary FPH levels (p > 0.05), except for the pellet durability index (PDI). Furthermore, the diets with 1% and 2% FPH were more palatable to fish than other treatment diets. The total bacteria (TB) in fish diets and guts followed an increasing trend with the increase in various levels of FPH in diets. The significantly highest body weight, specific growth rate (SGR), total biomass (TB), survival rate (SR), condition factor (CF), and hepatosomatic index (HSI) were noted in 2% FPH-fed fish when compared with other treatment groups (p